2015
DOI: 10.4209/aaqr.2014.10.0258
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Diurnal Variations of Fluorescent Bioaerosol Concentration and Size Distribution in the Urban Environment

Abstract: A recently introduced fluorescence based real-time bioaerosol instrument, BioScout, and an ultraviolet aerodynamic particle sizer (UVAPS) were used to study fluorescent bioaerosol particles (FBAP) in the Helsinki metropolitan area, Finland, during winter and summer. Two FBAP modes at 0.5-1.5 µm (fine) and 1.5-5 µm (coarse) were detected during the summer, whereas the fine mode dominated in the winter. The concentration and proportion of the coarse FBAP was high in summer (0.028 #/cm 3 , 23%) and low in winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 50 publications
2
40
1
Order By: Relevance
“…In addition, among the environmental factors, temperature, relative humidity, CO 2 concentrations, and particulate matter concentrations showed significant seasonal variations. Differences in temperature and relative humidity in the two seasons probably contributed to significant temporal variations in fungal spore concentrations (Kang et al, 2015;Saari et al, 2015). Our observations support the findings of previous studies: total fungal spore concentrations were higher during fall than during winter in a Norwegian grain and compound feed industry (Halstensen et al, 2013), and in Ohio, USA, the total fungal spore concentrations were higher during summer than during winter in swine and dairy farm environments (Lee et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, among the environmental factors, temperature, relative humidity, CO 2 concentrations, and particulate matter concentrations showed significant seasonal variations. Differences in temperature and relative humidity in the two seasons probably contributed to significant temporal variations in fungal spore concentrations (Kang et al, 2015;Saari et al, 2015). Our observations support the findings of previous studies: total fungal spore concentrations were higher during fall than during winter in a Norwegian grain and compound feed industry (Halstensen et al, 2013), and in Ohio, USA, the total fungal spore concentrations were higher during summer than during winter in swine and dairy farm environments (Lee et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Saari et al (2015) found that coarse fluorescent bioaerosol particles (1.5-5 µm) increased in summer, whereas in winter, these particles primarily existed in smaller particles (0.5-1.5 µm). The snow cover and decreased biological activity in winter resulted in the disappearance of microbes from the coarse fluorescent bioaerosol particles.…”
Section: Statistical Analysesmentioning
confidence: 97%
“…Both the WIBS and UV-APS, in various version updates, have been applied to many types of studies regarding outdoor aerosol characterization. For example, they have been important instruments: in the study of ice nuclei Mason et al, 2015;Twohy et al, 2016), toward the understanding of outdoor fungal spore concentrations (Gosselin et al, 2016;Saari et al, 2015a;O'Connor et al, 2015b), to investigate the concentration and properties of bioaerosols from long-range transport (Hallar et al, 2011), in tropical aerosol Whitehead et al, 2010Whitehead et al, , 2016Huffman et al, 2012;Valsan et al, 2016), in urban aerosol Saari et al, 2015b;Yu et al, 2016), from composting centers (O'Connor et al, 2015b), at high altitude Gabey et al, 2013;Perring et al, 2015;Ziemba et al, 2016), and in many other environments (Healy et al, 2014;Li et al, 2016;O'Connor et al, 2015a). The same instrumentation has been utilized for a number of studies involving the built, or indoor, environment as well (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%